Effects of inspiratory muscle training upon recovery time during high intensity, repetitive sprint activity - Romer, L. M.; McConnell, A. K.; Jones, D. A. (International Journal of Sports Medicine, 2002)
The present study examined the influence of specific inspiratory muscle training (IMT) upon recovery time during repetitive sprint activity, as well as the physiological and perceptual responses to fixed intensity shuttle running. Using a double-blind placebo-controlled design, 24 male repetitive sprint athletes were assigned randomly to either an IMT (n = 12) or placebo (n = 12) group. The self-selected recovery time during a repetitive sprint test and the physiological response to submaximal endurance exercise were determined. Following completion of baseline and pre-intervention measures, the IMT group performed 30 inspiratory efforts twice daily against a resistance equivalent to 50 % maximum inspiratory mouth pressure (MIP) for 6 wk. The placebo group performed 60 breaths once daily, for 6 wk, at a resistance equivalent to 15 % MIP, a load known to elicit negligible changes in respiratory muscle function. The IMT group improved total recovery time during the repetitive sprint test by 6.2 +/- 1.1 % (mean +/- SEM) above the changes noted for the placebo group (p = 0.006). Blood lactate and perceptual responses to submaximal exercise were also significantly attenuated following IMT (p </= 0.01). These data support existing evidence that specific IMT attenuates the blood lactate and perceptual responses to submaximal endurance exercise. In addition, the present study provides new evidence that IMT improves recovery time during high intensity, intermittent exercise in repetitive sprint athletes.